Social representations of nurses: Differences between incoming and outgoing Nursing students - Bastias, Franco Emmanuel (2020)
Objective. This article explored and compared social representations of nurses held by incoming and outgoing Nursing students in the Technical Nursing Program in San Juan, Argentina. Methods. Our research was descriptive and utilized the prototypicality method of analysis for social representations, from a structural approach. The sample was made up of 194 students (104 incoming and 90 outgoing), to whom we applied the word association technique for the term “nurse”. Results. Differences were found in the representations that incoming and outgoing students had. i) For incoming students: we observe a wide and general concept of a nurse, expressed in nonspecific terms such as “health” in the central core, while for outgoing students the term “care” emerged; ii) We infer distancing from the hegemonic medical model on the part of outgoing students, as well as an emphasis on the relational, as terms such as “vocation”, “humanization”, “love” and “empathy” are evoked, while the term “illness” decreases; iii) We understand that outgoing students highlight their autonomy with respect to doctors and nursing as a profession with the term “professional” with no mention of “assistance”, “help” and “assistant”, terms which did appear with incoming students; iv) Outgoing students convey a sense of a nurse’s diverse roles that go beyond the hospital setting, as instead of mentioning “hospital” and “injection” like incoming students, they mention “prevention” and “research”. Conclusion. The comparison of representative structures held by incoming and outgoing students suggests a transformation of self-image through a process of academic education.